United Arab Emirates “Iceberg Project” – would an ambitious concept comply with international law? (Ius Novum, 2022)
In the ongoing climate crisis, more and more states of the world undertake initiatives thatwould reduce negative impact of dangerous growth of global average temperature, includingdroughts, drowning of coastal cities and water shortage. Recently, an ambitious idea to providehuge supplies of water for the population of the United Arab Emirates was initiated by one ofEmirati businessmen – Mr Abdulla Alsheni, who plans to tow a huge Antarctic iceberg to thecoast of Emirates. The plan itself is a logistic challenge, but at the same time may raise certainconcerns on its compliance with international law. Hereby article has as an aim response toa question whether an act of towing an Antarctic iceberg would breach international lawprovisions, particularly those related to Antarctic Treaty System and law of the seas.
Keywords: iceberg, law of the seas, Antarctic Treaty System, climate change, international law